Late initiation of dialysis in diabetic Egyptian patients - Salwa Ibrahim; Hatem Darwish; Ahmed Fayed (SpringerOpen, 2015)
Introduction The number of chronic kidney disease (CKD) patients has been increasing over the past two decades, both globally and in Egypt. In our current study we tried to identify the pattern of end-stage renal patients [chronic kidney disease stage 5 (CKD5)], who presented at a tertiary referral center (Cairo University Hospital, Kasr-Alainy School of Medicine), to identify the epidemiological characteristics, clinical presentation, hospital course, and outcome. Patients and methods This is a prospective analysis of all medical admissions through the emergency department (Department 6) of Kasr-Alainy School of Medicine, Cairo University, in 1 year from July 2010 to July 2011. We included patients with proven CKD 5 who needed to be started on renal replacement therapy. Results A total of 571 patients were identified, of whom 82 patients (36 males and 46 females) proved to have CKD5 and needed to be started on renal replacement therapy. The mean age of the included patients was 51.63 ΁ 14.7 years. Oliguria and vomiting were the most frequent symptoms, as seen in 52 cases (63.4%), followed by symptoms of volume overload in 24 patients (29.3%) and disturbed level of consciousness and fever in six patients (7.3%). Diabetic nephropathy was the most common cause of renal failure in our studied cohort (51.2%), followed by hypertension (22%); the cause was unknown in 25% of patients. Four patients (4.9%) died during their hospital stay. Conclusion In Conclusion , our study showed that there is delayed referral for nephrology care and delayed initiation of dialysis when patients presented through the emergency department. Of particular interest was the fact that diabetic patients were most often subjected to this practice.